PELAKSANAAN PRIVATISASI BUMD DI ERA OTONOMI DAERAH DALAM SISTEM HUKUM DI INDONESIA - RHIDO JUSMADI (Jurnal Media Hukum, 2012)
Generally, the existing of Local Own Enterprise (LOE) was based on the willing of local government to intervene the economic life in that region. LOE as business instumen of the local government is valuable enough and gives benefits to the local development as part of the efforts to increase prosperous life in this era of regional autonomy. As stated in Indonesian Constitution 1945 Article 33, the local government (as representation of the state) has right to own LOE as company business. The need of owning this LOE by the local government is embodied in the Article 173 and 177 of the Law No. 32 of 2004. Privatisation now becomes an alternative that should be done by State Own Enterprise (SOE) but not by the LOE. It is because of there is, until now, no Law that regulates the privatisation in LOE. Now, the effort for privatisation still becomes the local policy of each local government. The policy of privatization, then, becomes the important need if it is based on the need to increase local government in the form of public services quality as well as increase its local budget development.